2019
DOI: 10.1039/c9ra04959b
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-based activated carbon as economic and efficient sustainable material for capacitive deionization of low salinity water

Abstract: Chitosan was selected as a carbonaceous precursor to prepare high-performance chitosan-based activated carbon (CTS-AC) for CDI electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The overlapping effect is reduced at a higher imposed voltage and salt concentration, ultimately resulting in better adsorption for a small pore size [ 414 ]. In addition to pore size optimization, current research is focused on controlling pore structure by using various calcination environments, e.g., ammonia [ 415 ], developing hierarchical porous biomass-derived carbon materials [ 416 , 417 , 418 ], and using MOF-derived materials [ 419 , 420 ] and biomass-derived materials [ 416 , 421 , 422 ]. The high surface area and tunable pore size of MOFs can be utilized to prepare electrode materials.…”
Section: Membrane Capacitive Deionizationmentioning
confidence: 99%
“…The overlapping effect is reduced at a higher imposed voltage and salt concentration, ultimately resulting in better adsorption for a small pore size [ 414 ]. In addition to pore size optimization, current research is focused on controlling pore structure by using various calcination environments, e.g., ammonia [ 415 ], developing hierarchical porous biomass-derived carbon materials [ 416 , 417 , 418 ], and using MOF-derived materials [ 419 , 420 ] and biomass-derived materials [ 416 , 421 , 422 ]. The high surface area and tunable pore size of MOFs can be utilized to prepare electrode materials.…”
Section: Membrane Capacitive Deionizationmentioning
confidence: 99%
“…Chitosan (Ch) is a biopolymer produced by deacetylation of regularly available biopolymer, chitin. Ch is a well-known source of AC with many applications, such as control drug delivery [ 8 , 9 ], heavy metal removal from water [ 10 , 11 ], hydrogen storage [ 12 ], catalytic and electrochemical plating [ 13 , 14 ], deionization of low-salinity water [ 15 ], pharmaceuticals residue removal [ 16 ], cationic and anionic dye adsorption [ 17 ], removal of pesticides [ 4 ], supercapacitor [ 18 ], and environmental applications [ 9 ]. In addition to the hydroxyl groups (–OH), Ch structure also contains amino groups (–NH 2 ) which is linked to a chain of six-member saccharide rings.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained S BET was 2025 m 2 /g and the N content was around 5 wt% [ 36 ]. In this context, many other researchers used KOH as activator for preparing a Ch-AC [ 12 , 13 , 14 , 15 , 37 , 38 ]. For example, Wrobel-Iwaniec et al activated Ch using KOH with different temperature (700 and 800 °C), and Ch-to-KOH ratios, and the resulting Ch-based ACs were of high S BET (922−3066 m 2 /g) and high V tot (0.40−1.38 cm 3 /g) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Biochar materials have been most widely applied in CDI electrodes, due to their wide range of sources, sustainable regeneration, excellent capacitance and low pollution. [10][11][12] Biomasses such as chitosan, 13 sugarcane, 14 Artocarpus peels, 15 bitter-tea and palm shell wastes, 16 and straw 3 have been widely used as precursors for preparing biochar materials. Chitin, which is second only to cellulose in yield, is an excellent raw material for biochar.…”
Section: Introductionmentioning
confidence: 99%
“…17 Most studies have shown that carbon materials with a high nitrogen content can improve the wettability of products, enlarging the accessible electrode area and enhancing charge accumulation, which is helpful for transferring charge during the electrosorption process and improves the specic capacitance. 13,18,19 In recent years, the modication of biochar has been a research hotspot in improving the electroadsorption capacity of biochar electrodes. The main methods include acidication, physical modication by high-temperature carbonization in an atmosphere furnace and chemical modication by adding chemical activators such as KOH, [20][21][22] ZnCl 2 , 23,24 etc.…”
Section: Introductionmentioning
confidence: 99%